Analysis of expressive and receptive kenyan sign language skills among primary deaf children in western region, kenya - Oracha Adoyo, Peter (2024)
Research has shown that deaf children of hearing parents, who constitu te 95% of the deaf community, find challenges in acquiring both sign a nd spoken languages. This study examined the competence of deaf childr en in Kenyan Sign Language. The study developed sign language tools in receptive and expressive vocabulary skills. These were sign order, co nversation, placement and picture descriptive as a measure. In the maj ority of the assessment task, there were clear indicators of age effec ts, family background whether-deaf or hearing, and amount of contact w ith skilled signers. In the interview section, children tended to answ er questions with short responses. The language was only reached at ag e ten. In a number of cases, simple questions were misunderstood and i rrelevant answers were given. It was noted that the interaction with d eaf children of deaf parents (DCDP) was very cordial as opposed to dea f children of hearing parents (DCHP). The picture description did not elicit proficient signing as was expected. The story description was n ot easy to understand and internalize because of the ambiguity of the children’s signing. This was because there was no indication of the pr otagonist. In sign order, ages ten to eleven did not seem to understan d spatial grammar reliably. This test worked better in its receptive v ersion. Article visualizations: